Stress corrosion cracking failure analysis of AISI 1018 carbon steel reinforcing bars in carbonated and chloride contaminated environment. (May 2023) - Martin, U.; Bastidas, D.M.
Highlights: Premature failure analysis of carbon steel reinforcement caused by SCC. Crack propagation rate more pH dependent than chloride induced. Precipitation of FeCO3 increases anodic dissolution kinetics. SCC susceptibility index (ISCC ) raised up to 60.4% for 4 wt% Cl − in carbonated solution. Miller-Smith mechanism promoting major transgranular cracking. Abstract: Herein, the premature failure analysis of AISI 1018 carbon steel reinforcing bars induced by stress corrosion cracking (SCC) and its pit-to-crack transition mechanism are presented. Service conditions under the influence of carbonation process and chloride contaminated environment are mimic to emulate pH drop and localized attack, respectively. The crack growth rate ( v crack ) was found to be more pH than chloride dependent, developing narrower and deeper cracks in high alkaline environment (pH 12.6), whereas short cracks were found in carbonated solution (pH 9.1). The formation of siderite (FeCO3 ) and further dissolution lead to ferric oxyhydroxide build up, enhancing the anodic kinetics by the local iron acid hydrolysis, increasing the dissolution rate, and promoting crack propagation after the stress intensity factor to develop SCC ( K ISCC ) was reached. Under carbonated conditions the SCC susceptibility increased over the alkaline, considerably reducing the mechanical performance. During the electrode straining, the recorded potential lied within the SCC risk zone and above the iron oxidation potential, allowing for the selective dissolution of grain boundaries that favors intergranular SCC through the ferrite/pearlite interface. Microcrack propagation found on pearlitic colonies followed the Miller-Smith mechanism, promoting major transgranular cracking.